2016
DOI: 10.1016/j.compfluid.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Transitional flow in intracranial aneurysms – A space and time refinement study below the Kolmogorov scales using Lattice Boltzmann Method

Abstract: Most Computational Fluid Dynamics (CFD) studies of hemodynamics in intracranial aneurysms are based on the assumption of laminar flow due to a relatively low (below 500) parent artery Reynolds number. A few studies have recently demonstrated the occurrence of transitional flow in aneurysms, but these studies employed special finite element schemes tailored to capture transitional nature of flow. In this study we investigate the occurrence of transition using a standard Lattice Boltzmann method (LBM). The LBM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…The dissipation in Patient2 is higher as sketched by u η , which demands for higher spatial and temporal resolutions. The t + is always lesser than 1.0 because of the intrinsically low δ t in the LBM algorithm . A review by Moin and Mahesh suggested that the smallest length scale that needs to be resolved for an accurate DNS of turbulent flows is required to be scriptOfalse(ηfalse).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dissipation in Patient2 is higher as sketched by u η , which demands for higher spatial and temporal resolutions. The t + is always lesser than 1.0 because of the intrinsically low δ t in the LBM algorithm . A review by Moin and Mahesh suggested that the smallest length scale that needs to be resolved for an accurate DNS of turbulent flows is required to be scriptOfalse(ηfalse).…”
Section: Resultsmentioning
confidence: 99%
“…The Kolmogorov length, time, and velocity scales are then respectively estimated as ηνfalse/u, τηνfalse/u2, uηu. On the basis of these scales, the quality of the spatial and temporal resolutions of a simulation is estimated by computing the ratio of δ x and δ t against corresponding Kolmogorov scales, i.e., l+=uδxν, t+=u2δtν. We remark that the Kolmogorov theory generally applies to a flow with infinitely large Reynolds number, when the turbulence is homogeneous and isotropic in nature. Our analysis is based on this theory for a surrogate estimate of the quality of the spatial and temporal resolutions, as has been done in previous works …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the failure to recognize this phenomenon in many previous computational studies, there is now considerable interest in evaluating (1) what CFD methods have accounted for this shortcoming and (2) how future studies must be tailored so that there is adequate resolution for their detection and analysis. [14][15][16] Computation of hemodynamic quantities becomes challenging in such a flow regime due to large and unpredictable temporal variations in flow characteristics. 17 In spite of recent developments in volumetric phasecontrast magnetic resonance angiography (PC-MRA) which allow instantaneous 3D velocity encoding, these techniques are still suboptimal to capture the transitional flow phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Furthermore in magnetic resonance (MR), even minor fluctuations in flow can lead to intravoxel dephasing where proton spins within the resolution cell become randomly oriented such that the accuracy of velocity measurements is significantly affected. 21 Computational hemodynamic modeling when performed on supercomputers, though capable of resolving the smallest spatial structures at minutest temporal scales, must be appropriately resolved according to the underlying flow regime, 14,15 and the stabilization schemes that might suppress the onset of flow-transition must be appropriately employed. 15 Currently, this as well as the limited computational availability makes it impossible to apply the insights into such highly resolved (HR) simulations in a clinical setting, though high resolution hemodynamic simulations remain a useful tool for basic and clinical research.…”
Section: Introductionmentioning
confidence: 99%